Mass balance estimates of carbon export in different water masses of the Chukchi Sea shelf. (August 2016) - Strong, Aaron L.; Lowry, Kate E.; Brown, Zachary W.; Mills, Matthew M.; van Dijken, Gert L.; Pickart, Robert S.; Cooper, Lee W.; Frey, Karen E.; Benner, Ron; Fichot, Cédric G.; Mathis, Jeremy T.; Bates, Nicholas R.; et al.
Abstract: We construct mass-balance based estimates of carbon (C) export fractions from the water column across the Chukchi Sea shelf. Export is calculated as the difference between phytoplankton drawdown of dissolved inorganic C (DIC) and the accumulation of autochthonous particulate and dissolved organic C in the water column. Organic carbon (Corg ) exports of >50% of DIC drawdown are ubiquitous across the shelf, even during, or shortly after, phytoplankton blooms, suggesting widespread and strong pelagic-benthic coupling. Export fractions on the shelf were generally greater in the less-productive Alaska Coastal Water than in the more productive Bering Shelf-Anadyr Water. Additionally, export fractions were greater in 2011 than in 2010, highlighting the significant spatial and inter-annual variability of the fate of Corg in this ecologically and biogeochemically important, and rapidly changing, ecosystem.